Partnering for success: Marrying social work with religion and culture - Kasiram, Ml; Partab, R (Social Work/Maatskaplike Werk, 2001)
The educational landscape in South Africa is changing rapidly in response to, amongst other factors, economic market conditions in the country (De Bard & Peck, 2000:3). Universities are urged to ensure their own survival within a macro-plan for rationalisation (Ministry of Education, 2001). At the University of Durban-Westville the discipline of S_ocial Work is housed in the Faculty of Health Sciences. The authors formed a partnership with the Faculty of Humanities, more specifically with the School of Rehgion and Culture, a merger that may seem unlikely. According to Robinson and Daigle (2000:26), unfamiliar mergers can be as potentially successful as those which are more conventionally likely. It appears that it is not the participating disciplines departments but the core ingredients of partnering that interplay to culminate in successful partnering. Postgraduate Theology students have joined Social Work postgraduate students in the Family Therapy and Practice module. As a result of this union, other meaningful liaisons have been born. The discipline and faculty marriage has been consummated, producing a healthy hybrid of students. Tough developmental hurdles are expected, but this article attempts to encourage further academic debate to help equip us to meet the challenge of partnering for profit.